FINANCIAL OUTCOMES OF ESG FRAMEWORK IMPLEMENTATION IN COMMERCIAL BANKS - Isakov Janabay Yakipbayevich (Ecominds Press, 2025)
The article examines the scientific and theoretical foundations of implementing ESG principles in commercial banks. In this regard, the situation in commercial banks, particularly in JSC “O’zsanoatqurilishbank”, has been analyzed, and the necessary discussions and conclusions have been made.
Keywords: ESG, commercial banks, sustainable development, “green” economy, risk.